Host-guest supramolecular chemistry in solid-state nanopores: potassium-driven modulation of ionic transport in nanofluidic diodes - Perez Mitta, Gonzalo (2015)
We describe the use of asymmetric nanopores decorated with crown ethers for constructing robust signal-responsive chemical devices. The modification of single conical nanopores with 18-crown-6 units led to a nanodevice whose electronic readout, derived from the transmembrane ion current, can be finely tuned over a wide range of K+ concentrations. The electrostatic characteristics of the nanopore environment arising from host-guest ion-recognition processes taking place on the pore walls are responsible for tuning the transmembrane ionic transport and the rectification properties of the pore. This work illustrates the potential and versatility of host-guest chemistry, in combination with nanofluidic elements, as a key enabler to achieve addressable chemical nanodevices mimicking the ion transport properties and gating functions of specific biological channels.